2009
DOI: 10.1007/s10898-008-9396-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Omega

Abstract: This paper considers the Omega function, proposed by Cascon, Keating & Shadwick as a performance measure for comparing financial assets. We discuss the use of Omega as a basis for portfolio selection. We show that the problem of choosing portfolio weights in order to maximize Omega typically has many local solutions and we describe some preliminary computational experience of finding the global optimum using a NAG library implementation of the Huyer & Neumaier MCS method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 7 publications
1
22
0
1
Order By: Relevance
“…The main reason is that maximizing the Omega ratio has been thought, until recently, to be computationally intractable and, as a consequence, most of the limited research has been focused on the design of heuristic algorithms. To the best of our knowledge, the first authors to investigate the use of the Omega ratio as a basis for portfolio selection are Kane et al [14]. The authors observe that the maximization of the Omega ratio leads to a non-convex and non-smooth optimization problem which has many local optima.…”
Section: The Omega Ratiomentioning
confidence: 99%
“…The main reason is that maximizing the Omega ratio has been thought, until recently, to be computationally intractable and, as a consequence, most of the limited research has been focused on the design of heuristic algorithms. To the best of our knowledge, the first authors to investigate the use of the Omega ratio as a basis for portfolio selection are Kane et al [14]. The authors observe that the maximization of the Omega ratio leads to a non-convex and non-smooth optimization problem which has many local optima.…”
Section: The Omega Ratiomentioning
confidence: 99%
“…In particular, Omega separately considers gains and losses without reference to a specific distribution for asset returns. For its implementation in portfolio construction see, for example, Avouyi-Dovi et al (2004), Passow (2005), Gilli et al (2006), Mausser et al (2006) and Kane et al (2009). Omega is defined for any portfolio return level as the probability weighted ratio of gains to losses relative to a threshold return defined by the investor, b r .…”
Section: Omega Optimization Modelmentioning
confidence: 99%
“…One example is the Omega function [8] which measures the performance of an asset, or of a portfolio of assets, by the ratio of the weighted gains (above a given threshold) over the weighted losses (below the threshold). Such function exhibits numerous discontinuities and recent studies involving its derivative-free optimization are reported in [15,18]. Another example arises in the tuning of algorithmic parameters for a given method/code (see [6] for instances where DSM have been applied to solve such problems) -the resulting objective functions are likely to exhibit all sorts of discontinuities given the way that typically a method/code responds to changes in its parameters.…”
Section: Introductionmentioning
confidence: 99%